1985
DOI: 10.1073/pnas.82.10.3242
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and nucleotide sequence of the alpha and beta subunits of allophycocyanin from the cyanelle genome of Cyanophora paradoxa.

Abstract: The genes for the a-and a-subunit apoproteins of allophycocyanin (AP) were isolated from the cyanelle genome of Cyanophora paradoxa and subjected to nucleotide sequence analysis. The AP a-subunit apoprotein gene was localized to a 7.8-kilobase-pair Pst I restriction fragment from cyanelle DNA by hybridization with a tetradecameric oligonucleotide probe. Sequence analysis using that oligonucleotide and its complement as priners for the dideoxy chain-termination sequencing method confirmed the presence of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…3A. For comparison, the analogous amino acid sequences from a eukaryotic alga, C. paradoxa (16,19) are shown. The intergenic region is 69 base pairs (bp) with stop codons present in two of the three reading frames.…”
Section: Identification and Characterization Of X-embl3 Genomicmentioning
confidence: 99%
See 1 more Smart Citation
“…3A. For comparison, the analogous amino acid sequences from a eukaryotic alga, C. paradoxa (16,19) are shown. The intergenic region is 69 base pairs (bp) with stop codons present in two of the three reading frames.…”
Section: Identification and Characterization Of X-embl3 Genomicmentioning
confidence: 99%
“…Each phycobiliprotein is composed of two related subunits, a and ,B, to which one or more tetrapyrole chromophores are attached (4), conferring upon each phycobiliprotein a characteristic light-absorption and emission spectrum. Amino acid (6)(7)(8)(9)(10)(11)(12)(13) and DNA (14)(15)(16) sequence data show considerable sequence conservation among the various phycobiliproteins (APC, PC, and phycoerythrin) as well as between the a and P3 subunits of a given phycobiliprotein. These findings suggest that phycobiliprotein genes arose via duplications of an ancestral sequence (8).…”
mentioning
confidence: 99%
“…, Pilot and Fox (1984) Walsh et al (1980) Lau et al (1987a), Kalla et al (1988) Wilson et al (1991) Anderson and Grossman (1990) Apt and Grossman (1993b) Minami et al (1985) Offner and Pilot and Fox (1984), Glazer (1987) Freidenreich et al (1978), Williams and Glazer (1978), Glazer (1987) Lau et al (1987b), Kalla et al (1988) Wilson et al (1991 Anderson and Grossman (1990) Sidler et al (1990) Apt and Grossman (1993b) Minami et al (1985) Offner and Troxler (1983) Bryant et al (1985) Sidler et al (1981, Riimbeli et al (1987) Houmard et al (1986, Klotz et al (1986) Su et al (1992 Some cyanobacteria are found under several names depending on the publications and the data banks. For clarity, only the most common used strain designations (from the point of view of the authors) have been used for the table above.…”
mentioning
confidence: 99%
“…DNA ligations, plasmid transformations, nick translations, and Southern (43) and plaque hybridizations were done by using standard procedures (27). All hybridizations included at least a 6-h prehybridization in 6x SET (lx SET is 150 mM NaCl, 30 (4,9).…”
mentioning
confidence: 99%